As Children of Adam: (Re)Discovering a History of Covenantal Pluralism in Afghan Constitutionalism - Kakar, Palwasha L. (The review of faith & international affairs, 2021)
This article (re)discovers a hidden history of religious pluralism in Afghanistan. First, through exploring the history of Hanafi Islam centered on the idea of “adamiyyah”; and second, through an analysis of the constitutional manifestations of these religious ideas of equality in two constitutions, Amir Amanullah's in 1923 and Nadir Khan's in 1931. These take center stage in this article after a rich discussion of ideas of equality in Hanafi Islam. In this moment, as peace negotiations continue, it is necessary to explore the hidden history of religious pluralism in Afghanistan. This pluralist past may help create a peaceful future.